Diagnostic accuracy of urinary cytokeratin fragment-19 (CYFRA21-1) for bladder cancer - Setianingsih, Yennie A.; Djatisoesanto, Wahjoe; Laksita, Tetuka B.; Aryati, Aryati (Narra J, 2024)
Bladder cancer is known for its high recurrence rate and requires constant patient monitoring. To confirm the diagnosis, a tissue sample from a cystoscopy is required, which the patient often avoids. Urine has the potential to be utilized as a diagnostic fluid because of its non-invasive nature and various biomarker contents. The aim of this study was to determine the diagnostic value of cytokeratin fragment-19 (CYFRA21-1) level in urine for diagnosing bladder cancer. This single-center cross-sectional study was performed with eligible inclusion were adults aged ≥18 years who presented with hematuria and suspected bladder cancer from imaging. Patients with a history of intravesical chemotherapy, radiotherapy and immunotherapy were excluded. Urine samples were collected prior to the cystoscopy. Detection of urinary CYFRA21-1 was carried out using the ELISA method. Of 154 patients included in the study, the diagnosis of bladder cancer was confirmed in 92 patients. Patients with bladder cancer had significantly higher urinary CYFRA21-1 levels compared to the non-bladder cancer group. The sensitivity, specificity, positive and negative predictive value, and positive likelihood ratio of the CYFRA21-1 were 80.4%, 43.5%, 67.9%, 60% and 1.425, respectively. The area under the curve for CYFRA21-1 was 0.608, computed from a receiver operating curve with a cut-off value of 13.3 ng/mL. In conclusion, urinary CYFRA21-1 levels have moderate diagnostic accuracy in determining bladder cancer among suspected individuals. Due to its high sensitivity, this biomarker could potentially be used alongside other screening tools for bladder cancer detection.